2006
DOI: 10.2134/agronj2005.0173
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biomass Turnover in Indian Subtropical Soils under Different Sugarcane Intercropping Systems

Abstract: Changes in soil organic C (C org ), total N (N t ), available nutrients, soil microbial biomass C (C mic ) and N (N mic ), and mineralizable C and N in the sugarcane (Saccharum officinarum L.) rhizosphere were evaluated under intensive sugarcane cropping systems with intercrops including wheat (Triticum aestivum L.), maize (Zea mays L.), rajmash (Phaseolus vulgaris L.), green gram [Vigna radiata (L.) R. Wilczek var. radiata], cowpea [Vign aunguiculata (L.) Walp.], lentil (Lens culinaris Medik.), mustard (Brass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 45 publications
5
16
0
2
Order By: Relevance
“…Thus the initially observed N immobilization during the pre-sugarcane cropping period, due to the high C:N ratio of the sugarcane residues applied (Hemwong et al 2008), persisted into the sugarcane growing period. The size of microbial biomass N in our experiment was similar to that reported by Suman et al (2006) under different sugarcane intercropping systems in India. Indeed the relationship between soil mineral N and sugarcane yield confirmed the dependency of sugarcane performance on soil N availability.…”
Section: Sugarcane Stover Management Effectssupporting
confidence: 89%
“…Thus the initially observed N immobilization during the pre-sugarcane cropping period, due to the high C:N ratio of the sugarcane residues applied (Hemwong et al 2008), persisted into the sugarcane growing period. The size of microbial biomass N in our experiment was similar to that reported by Suman et al (2006) under different sugarcane intercropping systems in India. Indeed the relationship between soil mineral N and sugarcane yield confirmed the dependency of sugarcane performance on soil N availability.…”
Section: Sugarcane Stover Management Effectssupporting
confidence: 89%
“…Such results increase in microbial biomass C, N and P due to organic matter were also reported by Ruess and Seagle (1994), Ghoshal and Singh (1995), Singh and Singh (1995) and Ros et al (2003). The range of C mic (186-320 lg g -1 soil) in the present study was comparable to 85.5-537 lg g -1 soil under P. cineraria under arid conditions (Nagarajan and Sundaramoorthy, 2000), 203-255 lg g -1 soil under Bactris, Hevea and polyculture based agroforestry Table 3 Annual microbial nutrient fluxes (kg ha -1 year -1 ) through C mic , N mic , P mic and dehydrogenase (p Kat kg -1 soil) and alkaline phosphatase activity (lml PNP s -1 ) under MPTs based agroforestry system land uses Values not marked with the same superscript letter are significant (P \ 0.01) using Tukeys HSD test Agroforest Syst (2011) 81:195-202 199 (Kurzatkowski et al 2004) and 193-267 lg g -1 soil under Indian subtropical soils (Suman et al 2006). The higher amount of microbial biomass C, N and P under P. cineraria might be due to greater micro fungal biomass than under other MPTs as reported by Nagarajan and Sundaramoorthy (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Organic management promotes microbial C and, thereby, soil C sequestration potential. Suman et al (2006) have shown changes in sugarcane rhizosphere soil quality due to intercropping by different crops and their residue incorporation. The incorporation of labile C substrates, such as pulses, led to improved yield and N mineralization, and the buildup of a secondary C pool and microbial C demonstrated, in the case of cereals, mustard and potato, that intercropping can promote long-term stability.…”
Section: Discussionmentioning
confidence: 99%